2010
DOI: 10.1186/1471-2377-10-116
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin, the lidocaine plaster and duloxetine in patients with refractory neuropathic pain: a systematic review

Abstract: BackgroundPatients frequently fail to receive adequate pain relief from, or are intolerant of, first-line therapies prescribed for neuropathic pain (NeP). This refractory chronic pain causes psychological distress and impacts patient quality of life. Published literature for treatment in refractory patients is sparse and often published as conference abstracts only. The aim of this study was to identify published data for three pharmacological treatments: pregabalin, lidocaine plaster, and duloxetine, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(45 reference statements)
1
9
0
2
Order By: Relevance
“…Relevant improvements in anxiety, depression, subjective sleep quality, and quality of life were observed after treatment with add-on pregabalin. This improvement in other dimensions of neuropathic pain is consistent with what it is known from randomized clinical trials in patients with neuropathic pain [9] and from previous studies on patients with refractory neuropathic pain [12, 14, 17, 40]. …”
Section: Discussionsupporting
confidence: 89%
“…Relevant improvements in anxiety, depression, subjective sleep quality, and quality of life were observed after treatment with add-on pregabalin. This improvement in other dimensions of neuropathic pain is consistent with what it is known from randomized clinical trials in patients with neuropathic pain [9] and from previous studies on patients with refractory neuropathic pain [12, 14, 17, 40]. …”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, pregabalin has been successfully used in patients with refractory NP [41, 42], which may be the case in some patients in the current study, since they were symptomatic despite using a mean 2.4 drugs. Specifically, in the Spanish primary care setting, pregabalin was shown to be an effective therapy for the treatment of peripheral NP in patients refractory to at least one previous analgesic in routine clinical practice [43, 44].…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, significant pain reduction was reported in all 7 of the studies involving pregabalin, while only one study using lidocaine reported a significant reduction; there was only one study with duloxetine. 88 …”
mentioning
confidence: 97%
“…85 Plested et al performed a systematic review of pregabalin, a lidocaine plaster and duloxetine in patients with refractory neuropathic pain. 88 It included four of the 5 studies with pregabalin mentioned above and 3 studies published only as abstracts. According to the authors, significant pain reduction was reported in all 7 of the studies involving pregabalin, while only one study using lidocaine reported a significant reduction; there was only one study with duloxetine.…”
mentioning
confidence: 99%